Low rates of patient-reported outcome claims for orphan drugs approved by the us food and drug administration - Szymon Jarosławski; Pascal Auquier; Borislav Borissov; Claude Dussart; Mondher Toumi (Taylor & Francis Group, 2018)
Background: Claims included in package inserts (PIs) for medicinal products approved by the US Food and Drug Administration (FDA) constitute the regulatory definition of drugs' benefits and risks. Objective: We sought to assess the usage of patient-reported outcome (PRO) claims in a comprehensive set of US FDA orphan drug approvals dated between 1/1/2012 and 31/12/2016, and characterize them. Study design: Orphan drug approval documentation was obtained from the US FDA website. Drug Package Inserts (PI) were analyzed to extract information on PRO-related language. Results: Among 178 drugs that met inclusion criteria, 16 (9%) products approved for 16 orphan indications contained PRO language in the Clinical Studies section of the PI. All PRO instruments concerned disease symptoms, and two also referred to patient functioning. The most common PRO instrument was a bleed-specific rating scale for four products approved for the treatment or prevention of bleeding episodes in patients with genetic bleeding disorders. Conclusions: There is a need to implement public incentives for academic development of PRO instruments for rare conditions and for regulatory policies that mandate the collection of PRO endpoints in pivotal trials of orphan drugs.